VD_FINDINFO Décision / 2013 / 216 vom 25. Februar 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, PROLONGATION, RETRAITVOIE DE DROIT | 221 CPP (CH), 222 CPP (CH), 227 CPP (CH), 386 al. 2 let. b CPP (CH)